Serum leptin might be causally correlated to invasive ductal breast carcinoma - Al-Shibli, Saad M.; Amjad, Nasser Muhammad; Al-Kubaisi, Muna Khaleel Dheyab; Harun, Norra; Nafie, Emad M.; Mizan, Shaikh (SciTechnol, 2018)
Introduction: Leptin, the hormone secreted from white adipose tissue is suspected of being a causative factor in tumorigenesis invarious tissues. Thus it might be a link between obesity and breastcancer. Objectives: In this project we tried to study causative association ofobesity and serum leptin with invasive ductal breast cancer (IDC) in a sample of Malaysian population. Methods: We measured various obesity parameters, and estimated serum leptin levels in a group of healthy control and IDC patients.After confirming diagnosis by standard histopathological methods, serum leptin levels were estimated using ELISA. Both the pre-and postoperative leptin levels were measured with the Patient group.